A 2-year randomised, double-blind, placebo-controlled, multicentre study of oral selective iNOS inhibitor, cindunistat (SD-6010), in patients with symptomatic osteoarthritis of the knee. Issue 2 (10th November 2012) - Hellio le Graverand, Marie-Pierre; Clemmer, Ray S; Redifer, Patricia; Brunell, Robert M; Hayes, Curtis W; Brandt, Kenneth D; Abramson, Steven B; Manning, Pamela T; Miller, Colin G; Vignon, Eric
Abstract : Objective: To determine if inhibition of inducible nitric oxide synthase (iNOS) with cindunistat hydrochloride maleate slows progression of osteoarthritis (OA) Methods: This 2-year, multinational, double-blind, placebo-controlled trial enrolled patients with symptomatic knee OA (Kellgren and Lawrence Grade (KLG) 2 or 3). Standard OA therapies were permitted throughout. Patients were randomly assigned to cindunistat (50 or 200 mg/day) or placebo. Randomisation was stratified by KLG. Radiographs to assess joint space narrowing (JSN) were acquired using the modified Lyon-schuss protocol at baseline, week 48 and 96. Results: Of 1457 patients (50 mg/day, n=485; 200 mg/day, n=486; placebo, n=486), 1048 (71.9%) completed the study. Patients were predominantly women; 56% had KLG3. The primary analysis did not demonstrate superiority of cindunistat versus placebo for rate of change in JSN. In KLG2 patients, JSN after 48 weeks was lower with cindunistat 50 mg/day versus placebo (p=0.032). Least-squares mean±SE JSN with cindunistat 50 mg/day ( −0.048±0.028 mm) and 200 mg/day (−0.062±0.028 mm) were 59.9% (95% CI 6.8% to 106.9%) and 48.7% (95% CI -8.4% to 93.9%) of placebo, improvement was not maintained at 96 weeks. No improvement was observed for KLG3 patients at either time-point. Cindunistat did not improve joint pain or function, but was generally well tolerated. Conclusions: Cindunistat (50 or 200 mg/day) did not slow the rate of JSN versus placebo. After 48-weeks, KLG2 patients showed less JSN; however, the improvement was not sustained at 96-weeks. iNOS inhibition did not slow OA progression in KLG3 patients. Clinical trial listing: NCT00565812